Manufacturing Processes 1 Cutting - Klocke, Fritz; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
The book series on manufacturing processes for engineers is a reference work for scientific and industrial experts. This volume on Turning, Milling and Drilling starts from the basic principles of machining with geometrically defined cutting edges based on a common active principle. In addition, appropriate tool designs as well as the reasonable use of cutting material are presented. A detailed chapter about the machinability of the most important workpiece materials, such as steel and cast iron, light metal alloys and high temperature resistant materials imparts a broad knowledge of the interrelations between workpiece materials, cutting materials and process parameters. This book is in the RWTHedition Series as are the other four volumes of the reference work.
Introduction -- Metrology and workpiece quality -- Fundamentals of cutting -- Cutting materials and tools -- Finite element method (FEM) -- Cutting fluids -- Tool life behavior -- Process design and Process monitoring -- Processes with rotational primary movement -- Processes with translatory primary movement -- Bibliography -- Index.
Keywords: Engineering; Industrial engineering; Machinery; Structural control (Engineering).; Surfaces (Physics).; Engineering; Operating Procedures, Materials Treatment; Characterization and Evaluation of Materials; Industrial and Production Engineering; Manufacturing, Machines, Tools